Racial and Ethnic Disparities Among Participants in US-Based Phase 3 Randomized Cancer Clinical Trials. Issue 5 (7th July 2020) - Grant, Stephen R; Lin, Timothy A; Miller, Austin B; Mainwaring, Walker; Espinoza, Andres F; Jethanandani, Amit; Walker, Gary V; Smith, Benjamin D; Ashleigh Guadagnolo, B; Jagsi, Reshma; David Fuller, C; Thomas, Charles R; et al.
Abstract: Although improving representation of racial and ethnic groups in United States clinical trials has been a focus of federal initiatives for nearly 3 decades, the status of racial and ethnic minority enrollment on cancer trials is largely unknown. We used a broad collection of phase 3 cancer trials derived from ClinicalTrials.gov to evaluate racial and ethnic enrollment among US cancer trials. The difference in incidence by race and ethnicity was the median absolute difference between trial and corresponding Surveillance, Epidemiology, and End Results data. All statistical tests were 2-sided. Using a cohort of 168 eligible trials, median difference in incidence by race and ethnicity was +6.8% for Whites (interquartile range [IQR] = +1.8% to +10.1%; P < .001 by Wilcoxon signed-rank test comparing median difference in incidence by race and ethnicity to a value of 0), -2.6% for Blacks (IQR = -5.1% to +1.2%; P = .004), -4.7% for Hispanics (IQR = -7.5% to -0.3%; P < .001), and -4.7% for Asians (IQR = -5.7% to -3.3%; P < .001). These data demonstrate overrepresentation of Whites, with continued underrepresentation of racial and ethnic minority subgroups.